1986
DOI: 10.1144/gsl.sp.1986.021.01.28
|View full text |Cite
|
Sign up to set email alerts
|

Organic-rich sedimentation at the Cenomanian-Turonian boundary in oceanic and coastal basins in the North Atlantic and Tethys

Abstract: Summary One of the most striking results of the Deep Sea Drilling Project is the proof that organic-rich sediments have a widespread geographical distribution during the period from Upper Cenomanian to Middle Turonian. Such sediments were drilled at North Atlantic DSDP Sites: 105, 135, 137, 138, 367, 398, 551, 603. They are also present (from outcrops or oil wells) on the shelf of the African continental margin (Senegal, Tarfaya and Agadir Basins), in the Tethys (former Alboran Block, Southern Spain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 33 publications
9
65
0
1
Order By: Relevance
“…9) (E. G. Kauffman, pers, comm., 1987). Similar sequences are commonly recorded from other sites in the deeper North Atlantic, as well as from onshore outcrops in Europe and northwest Africa (compilation in Herbin et al, 1986b). Examples include the southern part of the Galicia mar gin at Deep Sea Drilling Project (DSDP) Site 398 (Fig.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…9) (E. G. Kauffman, pers, comm., 1987). Similar sequences are commonly recorded from other sites in the deeper North Atlantic, as well as from onshore outcrops in Europe and northwest Africa (compilation in Herbin et al, 1986b). Examples include the southern part of the Galicia mar gin at Deep Sea Drilling Project (DSDP) Site 398 (Fig.…”
Section: Introductionsupporting
confidence: 70%
“…SEM studies revealed the typical fissile character of the CTBE black shales with scattered pyrite crystals or framboids of pyrite. Samples from Section 398D-56-2 have the typical organic geochemistry characteristics: total or ganic carbon reaches 10% and the organic matter is of domi nantly marine origin (amorphous kerogen; Herbin et al, 1986b). Habib (1979b) described the interval as belonging to his xeno morphic palynofacies type (amorphous palynodebris composed mostly of optically translucent yellow, brown, and orange parti cles), which supports the organic geochemistry results.…”
Section: Site 398supporting
confidence: 60%
See 2 more Smart Citations
“…3) is one of the largest and best documented carbon-isotope events in the geological record (Jenkyns, 1980(Jenkyns, , 1985Scholle & Arthur, 1980;Schlanger et al 1987). This event is conventionally interpreted as being related to accelerated burial of marine organic matter, particularly in the Atlantic, but also in other ocean basins (Herbin et al 1986;Arthur et al 1990;Kuypers et al 2002Kuypers et al , 2004. The phenomenon is widely referred to as the Cenomanian/Turonian Boundary Event (CTBE), or Oceanic Anoxic Event 2 (OAE2; Arthur et al 1990).…”
Section: A11 Cenomanian/turonian Boundary Eventmentioning
confidence: 99%